Pemaknaan Ihdad Perspektif Hadits dan Relevansinya terhadap Budaya Pop dengan Pendekatan Interkonektif - Mauliyanti; Nasrulloh (Al-Kindi, 2026)
This study examines ihdad in classical hadith and its relevance for Generation Z living in pop culture and the digital space. Normatively, the ihdad hadith establishes strict rules regarding the prohibition of adornment and restrictions on activities during the mourning period. However, Gen Z's expressions of grief tend to be open, visual, and influenced by social media aesthetics, creating tensions with traditional ihdad norms. This study addresses four research questions: the interpretation of the classical ihdad hadith, the characteristics of pop culture and Gen Z's expressions of grief, the dynamics of their interaction, and solutions through an interconnected approach. Using a literature review method, the study found that ihdad can be understood more contextually by emphasizing its moral and spiritual values. An interconnected approach offers a bridge between normative teachings and digital cultural practices, ensuring that ihdad remains relevant and adaptive for Gen Z.